Diagnosis of internal combustion engine based on mechanical noise - S. Kapitonov, Sergei; Y. Grigorovich, Sergei; A. Medvedev, Sergei; I. Kurbakov, Ivan (International Journal of Engineering and Technology, 2018)
The work of sensors is investigated in the article when they are used to detect malfunctions of automobile engines by the method of analyzing noise spectrum. The method of diagnostics of internal combustion engines for noise and vibration has been developed. This method allows to determine the fault at an early stage in a short period of time (the diagnostic process takes 5-10 minutes). The proposed solution allows to reduce the degree of influence of the human factor. Such an approach to diagnostics makes it possible to determine a huge number of faults due to the use of modern computer technologies. There is no need to dismantle the unit to determine a malfunction, which also contributes to a significant reduction in overall repair time. The model of the hardware part of the complex is based on the developed method for diagnosing engine malfunctions by noise and vibration. Technologies of National Instruments were used to create the layout. The program part is developed in the visual programming environment LabVIEW. The investigation of different types of noise sensors for use in the measuring complex was carried out using the developed hardware and software. Three types of noise sensors were investigated. The conclusion can be drawn based on the results of the study, that a piezoelectric pickup is better suited for diagnosing or analyzing noise. The analysis of the most frequently encountered car faults was carried out with the aim of forming real engine operating modes and testing the model.